Design of a Robotic Rollator for Sit-To-Stand and Walking Assistance of Older Individuals with Mobility Disorders - Mahdi, Anas (University of Waterloo, 2022)
Many elderly people suffer from a loss of mobility due to musculoskeletal disorders, neurological conditions, diabetes, frailty, or other impairments, and thus require assistance during walking and Sit-to-Stand (STS) transfers. Majority of commercially available mobility assistance devices are passive walkers, rollators, and canes which provide limited walking support and minimum support while standing up. Persons needing STS assistance typically rely on external forces applied by a person or a device to help them stand up. In this thesis, we will present the design and functionalities of SkyWalker, a novel lightweight robotic rollator with active STS assistance. It is made for providing powered walking support on different terrains. STS support relies on a bilevel handle design and consists of active vertical lift and forward translation support during STS, then a handle change by the user to fixed handles once standing. Stand-to-Sit transfer follows the reverse order. To evaluate the SkyWalker design and control and identify areas of improvement, we conducted experiments with healthy young adult subjects. A biomechanical study on STS motions compared 6 different STS trajectories for which the kinematic, kinetic, and user feedback were collected. Additionally, we tested SkyWalker's ability to support walking on different surfaces, on uneven terrain, and around obstacles. Finally, we conducted an interaction study to test voice control as a potential interface to allow the user to control the direction and movement of SkyWalker independently. The experiments showcased the walker as a potential assistive device and identified limitations to be addressed prior to experiments with frail subjects. The data collected and the feedback from the subjects show great potential for the robot to be used as an assistive device in an indoor and outdoor environment.
Keywords: assistive technology; biomedical engineering; physical human-robot interaction; sit-to-stand; robotics; walking aid